Effects of HIV/AIDS on Agricultural Produce in Nassarawa Eggon Local Government Area Nigeria - Iliya Dan Iliya (Solo International Collaboration and Publication of Social Sciences and Humanities, 2024)
This study investigated the effect of HIV/AIDS on agricultural output in the local government area of Nassarawa Eggon in the State of Nasarawa. Data were collected from 360 respondents and analysed using the Generalized Method of Moments regression model and descriptive statistics. The study found that HIV/AIDS reduced the output and income of affected farmers largely due to lost labour hours for agriculture due to HIV/AIDS and; labour costs wages due to HIV / AIDS; The study recommends that governments at state and local levels should design and implement financial inclusion programs and register vulnerable groups especially HIV/AIDS households.  Finally, the study recommends that the government should resurrect measures that will stop the spread of the disease among Nassarawa Eggon farmers to reduce the farmers' lost working hours. This will increase the output and income level of affected farmers.